Can mutation abundance assess the biological behavior of BRAF V600E-positive papillary thyroid carcinoma? - Yeqin Ni; Ping Song; Xiangfeng Lin; Jingjing Shi; Qian Shi; Yuanhui Li; Siyu Zhu; Tianhan Zhou; Yanping Xun; Shirong Zhang; Xingchang Ren; Kaining Lu; et al. (Journal of Translational Medicine)
Abstract Background BRAF V600E mutation is the most common genetic change in papillary thyroid carcinoma (PTC). Nevertheless, the association between BRAF V600E mutation status and abundance and the biological behavior of PTC is unclear. Thus, this study investigated whether BRAF V600E mutation status and abundance are related to PTC biological behavior and whether BRAF V600E mutation abundance can be used to further stratify risk. Methods Postoperative formalin-fixed paraffin-embedded (FFPE) specimens from 528 PTC patients formed the retrospective cohort, and preoperative fine-needle aspiration (FNA) specimens from 167 PTC patients formed the prospective cohort. Furthermore, 74 FNA specimens were collected from two additional hospitals to form the external cohort. Droplet digital polymerase chain reaction (ddPCR) was used to detect BRAF V600E mutation status and abundance in the two types of specimens. The relationship between BRAF V600E mutation status and abundance and PTC biological behavior was analyzed in the cohorts. To predict BRAF V600E-positive PTC risk stratification, we constructed postoperative clinicopathological models (Model A, retrospective; Model B, prospective), a preoperative clinical model (Model C), and a fusion model combining BRAF V600E mutation abundance and preoperative clinical information (Model D). The area under the curve (AUC) values were used to assess the performance of these models. Results Univariate and multivariate analysis of the retrospective, prospective and external cohorts indicated that BRAF V600E mutation abundance, not status, was significantly associated with PTC biological behavior. An increase in BRAF V600E mutation abundance was significantly associated with an increased risk of BRAF V600E-positive PTC. The AUCs of model A, model B, model C, and model D in the validation sets were 0.89 (95% CI, 0.83–0.94), 0.89 (95% CI, 0.83–0.99), 0.65 (95% CI, 0.48–0.82), and 0.86 (95% CI, 0.75–0.98), respectively. The AUCs of model B, model C, and model D in the external sets were 0.78(95% CI, 0.67–0.88), 0.61(95% CI, 0.48–0.75) and 0.82 (95% CI, 0.71–0.93), respectively. The AUC of model D was higher than that of model C in the external validation set by 21% (P = 0.02). Conclusions BRAF V600E mutation abundance, not status, reflects PTC biological behavior. Integrating BRAF V600E mutation abundance and preoperative clinical information can be used to better preoperatively predict BRAF V600E-positive PTC risk and guide clinical decision making. Trial registration ChiCTR, ChiCTR2300071472. Registered 31 July 2016 - Retrospectively registered, https://www.chictr.org.cn/showproj.html?proj=190478 .